The rise and fall of the alveolar process: Dependency of teeth and metabolic aspects. (December 2018) - Jonasson, Grethe; Skoglund, Ingmarie; Rythén, Marianne
Highlights: The alveolar bone has a unique capacity to follow a tooth's spontaneous and orthodontic movements. The mandibular alveolar process has the skeleton's fastest bone metabolism. Early detection of osteoporosis and fracture risk is possible in the mandible. Mandibular bone morphology can predict osteoporotic (not mandibular) fractures. Maintaining mandibular teeth is important. Abstract: The alveolar bone has a unique capacity to follow the teeth's movements. It is formed around erupting teeth and their periodontal ligaments: the more the teeth have erupted, the larger the alveolar process. Throughout life the teeth erupt and migrate in an occlusal and mesial direction to compensate for attrition, an evolutionary trait. After tooth extraction, the alveolar process is resorbed to varying degrees. The mandibular alveolar bone mirrors skeletal bone condition. Due to fast bone turnover (which is the fastest in the whole skeleton), low bone mass and increased fracture risk may first be seen here. If a periapical radiograph of the mandibular premolars shows a dense trabeculation with well-mineralized trabeculae and small intertrabecular spaces, it is a reliable sign of normal skeletal bone density (BMD) and low skeletal fracture risk, whereas a sparse trabecular pattern indicates osteopenia and high fracture risk. The bone turnover rate in the mandible is twice that of the maxilla, and may, hypothetically, play a role in the development of osteonecrosis of the jaw (ONJ), which has been found mainly in the mandibular alveolar process?